Дослідження властивостей низькочастотних коливань на основі синхронізованих векторних вимірів - Яндульський, О.С.; Марченко, А.А.; Мацейко, В.В. (Технічна електродинаміка, 2014)
Розглянуто актуальні питання дослідження низькочастотних коливань потужності в ОЕС України в умовах впровадження сучасних систем моніторингу перехідних режимів. Представлено результат співставлення розробленого алгоритму ідентифікації домінуючих частот коливань та розрахунку їх параметрів, що базується на використанні синхронізованих векторних вимірів, з традиційним розрахунком коливальних властивостей енергосистем методом модального аналізу в програмному середовищі Power Factory фірми DigSilent. Проведено аналіз основних властивостей та визначено рівень небезпеки виявлених коливань з точки зору демпфірування коливань. Рассмотрены актуальные вопросы исследования низкочастотных колебаний мощности в ОЭС Украины в условиях внедрения современных систем мониторинга переходных режимов. Представлен результат сопоставления разработанного алгоритма идентификации доминирующих частот колебаний и расчета их параметров, основанного на использовании синхронизированных векторных измерений, с традиционным расчетом колебательных свойств энергосистем методом модального анализа в программной среде Power Factory фирмы DigSilent. Проведен анализ основных свойств и изображен уровень опасности выявленных колебаний с точки зрения демпфирования колебаний. Increased progress of power systems has led to a structure of close generator groups connected to other groups by weak transmission lines. This has been known to cause oscillations were these groups oscillate against each other in an inter area fashion. This implies that power oscillates between areas and thus diminishes the transmission capability of the interconnected system. This paper describes the identifying modes of oscillations in interconnected power systems by means of using recordings of a Wide Area Measuring System. To detect the dominant oscillation frequency, the Fast Fourier Transform is applied. The algorithm is tested on known test system and results were compared with the results of modal analysis of power system. It is obvious from the analysis that further investigations are necessary to improve system damping. This is an important goal not only to ensure reliable system operation but also to improve transmission capacity of the grid with the existing high voltage lines.